2017
DOI: 10.17265/2328-7136/2017.01.006
|View full text |Cite
|
Sign up to set email alerts
|

A gamma analysis approach to determine optimal parameters for Monte Carlo simulation of 6MV Varian ClinaciX photon beam

Abstract: Monte Carlo (MC) method is the gold standard dose calculation algorithm. Determination of the electron beam parameters for MC simulation is often estimated using trial and error methods. However, this can be tedious and time-consuming. This paper aims to validate MC simulated data using 1D gamma analysis for 6MV photon beam to obtain the optimal parameters. BEAMnrc codes were used to generate phase space files for conventional field sizes 10 × 10 cm 2 , 6 × 6 cm 2 , 4 × 4 cm 2 and small field sizes 2 × 2 cm 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…The PDD showed more sensitivity to E than to FWHM. As other studies found, the effect of change in FWHM on PDD is insignificant,[ 26 27 ] since by increasing FWHM of incident electron beam only the width of bremsstrahlung photons beam increases and its energy remains constant. Therefore, the PDD, which is mainly affected by photon energy, is not affected significantly by FWHM [ Figure 5b ].…”
Section: Discussionmentioning
confidence: 81%
“…The PDD showed more sensitivity to E than to FWHM. As other studies found, the effect of change in FWHM on PDD is insignificant,[ 26 27 ] since by increasing FWHM of incident electron beam only the width of bremsstrahlung photons beam increases and its energy remains constant. Therefore, the PDD, which is mainly affected by photon energy, is not affected significantly by FWHM [ Figure 5b ].…”
Section: Discussionmentioning
confidence: 81%